Analisis Manajemen Wisata Religi Dalam Meningkatkan Daya Tarik Wisata Religi Syekh Rifa’i (GENTARU) Tuban - Kris Fitriana Wahyu Lesteri, Siti; Sefiana , Sinta (Department of Da'wah Management, Faculty of Da'wah, IAINU Tuban, 2025)
Syekh Rifa’i grave is in Tuwiri Wetan Village, Merakurak District, Tuban Regency, which is one of the religious tours in Merakurak District. With this research, it aims to review how the history of Sheikh Rifa’i or what is commonly called Sheikh Gentaru because according to the author many people are still unfamiliar with the history of Sheikh Rifa’i. Even though he has a very impressed history, one of which is making a spring with Sunan Bonang, and it can be used by the wider community until now. There are even those who take advantage of the flow as nature tourism, because of the clean and clear flow that comes from the spring, the spring is named Srunggo. What's more interesting is, from his history there is a myth that if a government comes to the tomb, it will step down. And that is a note from the manager of the tomb to dispel this myth, so that Sheikh Rifa’i's name will be clean again.